Evaluación de la terapia combinada, miel de abeja y panela, en cirugías de ovariohisterectomía en caninas, y sus posibles alteraciones hematológicas - Real García, Jhonatan Bladimir (2018)
The present investigation was conducted in the city of Guaranda, province of Bolívar, had as its theme "Evaluation of the combined therapy, honey and panela, in canine ovariohysterectomy surgeries, and their possible hematological alterations". The objectives were: To evaluate the effectiveness of the combination therapy, honey and panela, in wound healing, establish the wound healing time by applying the different treatments based on honey and panela, demonstrate the possible hematological alterations in the application of treatments T0, T1, T2 o T3. In the research, 40 surgeries were performed on female canines of different breeds, age and weight, It was applied topically in the wound, honey and panela every 12 hours after the surgeries, It was divided into 4 groups of 10 patients, in which, at T0 or control, no treatment was applied, with a mean of healing of 8.1 days, T1 or 5 gr of honey, had a mean healing of 5.5 days, T2 or 5 gr of panela, had a mean of 6.1 days and the T3 or 2.5 gr of honey of bee + 2.5 gr of panela, had an average of 5.4 days. Haematological alterations were measured by blood tests. Taking samples before and after 24 hours of the surgeries, finding alterations of leukocytes (leukocytosis) and neutrophils (neutrophilia). For the statistical representation of the results, an analysis of variance (ANOVA) was used, with which no significant differences were found between age, weight, race, wound size, degree of pain, degree of inflammation and haematological alterations, without However, at the time of healing it was possible to show that one treatment behaved differently from the T0 or control, while the other treatments obtained similar results.